Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Experience the convenience of getting accurate answers to your questions from a dedicated community of professionals. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Answer:
[tex]\sum_{n = 1}^{7} -2 -2n[/tex]
Step-by-step explanation:
Arithmetic sequence:
In an arithmetic sequence, the difference of consecutive terms is always the same, called common difference.
The nth term of a sequence is given by:
[tex]a_{n} = a_1 + (n-1)d[/tex]
In which [tex]a_1[/tex] is the first term and d is the common difference.
Sigma notation to represent the sum of the first seven terms
Sum going from the index starting at 1 and finishing at 7, that is:
[tex]\sum_{n = 1}^{7} f(n)[/tex]
Now we have to fund the function, which is given by an arithmetic sequence.
−4, −6, −8,
First term -4, common difference - 6 - (-4) = -6 + 4 = -2, so [tex]a_1 = -4, d = -2[/tex]
Then
[tex]f(n) = a_{n} = a_1 + (n-1)d[/tex]
[tex]f(n) = -4 + (n-1)(-2)[/tex]
[tex]f(n) = -4 - 2n + 2 = -2 - 2n[/tex]
Sigma notation:
Replacing f(n)
[tex]\sum_{n = 1}^{7} -2 -2n[/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.